Issues in guided exploratory learning from computer-based systems - Cox, Richard (1992)
Abstract: "Exploratory approaches to learning are being used increasingly in computer-based educational and vocational training systems. This paper examines recent evidence for the effectiveness of the approach in relation to a range of learning issues. It is suggested that systematic studies of guidance and advice giving by expert tutors are required to more fully understand how to provide effective support to learners. Several observational methodologies are outlined and the paper concludes with examples of how careful studies of tutor-student interaction can usefully inform the design of intelligent educational systems."
Keywords: Computer-assisted instruction